Innate and acquired control of trypanosome parasitaemia in Cape buffalo - Black, Samuel J.; Sicard, E.L.; Murphy, N.; Nolan, D. (Elsevier, 2001)
The review discusses the roles of serum xanthine oxidise serum catalase and trypanosome-specific immune responses in the regulation of the level of trypanosome parasitaemic waves in Cape buffalo. Topics of discussion include non-specific trypanocidal activity in cape buffalo serum; recurrence of psrasitaemia in Cape buffalo and a second resistance mechanism; antibodies against invariant antigens and their contribution to the control of parasitaemia in chronically infected Cape buffalo; and what immune responses in addition to antibody production might suppress trypanosome population growth in Cape buffalo.